COMET ASSAY FOR RAPID DETECTION OF DNA BASE DAMAGE IN PLANTS - & et al., Mahmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study was to evaluate the genotoxic effects of exposure to environmental agent’s pollutants in many doses data. The experimental data (1.553, 2.190: 1.515, 1.516) respectively, suggest that the DNA damage parameters (Tail length, Tail width l) were found higher value in exposed population when compared with the ratio of the length to width that cells exhibiting no decampment when having a ratio of one. The percentage and distribution of cells in exposed population also Proportional in values. This study demonstrates that, utilizing sensitive techniques, it is possible to detect environmental agent’s risks at an early stage.